2010
DOI: 10.1111/j.1475-1313.2009.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

pH dependent spectral properties of sodium fluorescein ophthalmic solutions revisited

Abstract: The present studies confirm and extend some earlier reports that pH (over the range of 4.0-8.5), as well as concentration, predictably determines the fluorescence emission of dilute aqueous solutions of NaF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 17 publications
2
55
0
1
Order By: Relevance
“…We therefore, adjusted the buffer to pH 5.44 for improved antioxidant stability. Due to the impact of pH on fluorescein light emissions (Doughty, 2010), for maintained sensitivity, we increased the concentration of fluorescein and AAPH as compared to previously published methods (Cao G, 1993). 75uL of 1.9uM fluorescein in a 75mM sodium acetate buffer (pH 5.44) were added to each well of the plate followed by 50uL of sample: diluted tea (0.09g/L), Trolox control (50uM) or buffer as a blank.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore, adjusted the buffer to pH 5.44 for improved antioxidant stability. Due to the impact of pH on fluorescein light emissions (Doughty, 2010), for maintained sensitivity, we increased the concentration of fluorescein and AAPH as compared to previously published methods (Cao G, 1993). 75uL of 1.9uM fluorescein in a 75mM sodium acetate buffer (pH 5.44) were added to each well of the plate followed by 50uL of sample: diluted tea (0.09g/L), Trolox control (50uM) or buffer as a blank.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, control measurements with fluorescein revealed comparable dependences of the fluorescence maximum intensity and position as in the APF experiments. Both effects can be explained by aggregation of fluorescein (47)(48)(49). Moreover, fluorescein shows pH-dependent fluorescence properties due to changes in the ratio of the mono-and dianionic form (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescein bound to intracellular proteins, including albumin, could reveal fluorescence quenching, both static and dynamic. In addition, Doughty 21 reported that the fluorescence of sodium fluorescein was clearly influenced by both pH and concentration. Both the absorption and resultant fluorescence declined as the pH is reduced from 8.5 to lower pH values.…”
Section: Discussionmentioning
confidence: 99%